Gathering Farmer-Pastoralist Livelihoods in Rhodesia: 1965–1980. (15th September 2019) - Kwashirai, Vimbai; Mwatwara, Wesley; Hove, Godfrey
This study analyses livelihoods and their sustainability among blacks in Northern Mount Darwin District (NMDD), Rhodesia, between 1965 and 1980. It explores livelihood streams gained from gathering multiple forest products, farming and keeping livestock in the context of severe land shortage. It examines major socio-economic challenges that were part and parcel of the exploitative colonial system: the international sanctions imposed on Rhodesia after the Unilateral Declaration of Independence (UDI) in 1965 and the economic problems associated with the war of liberation during the 1960s and 1970s. The study adopts several interdisciplinary research techniques including historical and case study approaches. The exploration of black livelihoods in the NMDD case study shows that the region suffered extreme state negligence in the provision of public services like education, health, roads, water and sanitation. The study privileges the Sustainable Livelihood Framework (SLF) that integrates assets, constraints and human capabilities in a logical and comprehensive manner to analyse the status, form, nature and condition of livelihoods in Rhodesia. Vulnerability to colonial oppression and exploitation were major factors that NMDD families endeavoured to manage through diverse ways of making a living dominated by farming.